Network-constrained flexible ramping product provision of prosumer aggregator: a data-driven stochastic bi-level optimization - Ai, Xin; Hu, Huanyu; Hu, Junjie; Wang, Zhe; Wang, Kunyu (Frontiers in Energy Research, 2023)
Prosumers are expected to provide the flexible ramping product(FRP) in the power system. However, voltage violations and line congestion may arise in the distribution network, when FRP delivered by prosumers. Hence, this paper proposes a data-driven stochastic bi-level optimization model to coordinate the prosumer aggregator to decide FRP-offering while ensuring distribution network security under FRP delivery. In the proposed bi-level model, the upper-level is a min-max problem, representing the minimum expected cost under the worst-case scenario probability distribution for the prosumer aggregator. The lower-level is the operation cost minimization within the distribution network security for distribution network operator. The proposed model is converted into a singlelevel model using the Karush-Kuhn-Tucker condition and strong duality theory, and applied to the modified IEEE 33-bus network with three prosumers. The results demonstrate the effectiveness of the proposed model.This is a provisional file, not the final typeset article Therefore, this paper investigate how prosumer aggregator can provide FRP while ensuring the security of the distribution network.The current definition of prosumer is broad, encompassing subjects such as electric vehicle aggregators, smart buildings, and grid-connected microgrids, which are also considered as prosumers(